A Scenario-Based Methodology for Analyzing the Ethical, Legal, and Social Issues in Genomic Data Sharing. (October 2020) - McWhirter, Rebekah; Eckstein, Lisa; Chalmers, Don; Critchley, Christine; Nielsen, Jane; Otlowski, Margaret; Nicol, Dianne
Sharing of genomic and associated data is essential to clinical practice and biomedical research, and is increasingly encouraged by journals and funding bodies. Grappling with the range of legal and ethical issues raised by genomic data sharing presents a significant challenge, given the diversity of practices: from defined sharing of individual patient data, to broad-scale public sharing of research data, to uploading of direct-to-consumer test data by community members. Most commentary to date has discussed these issues in broad terms, but the debate can only progress if we engage with more granularity, grounded in jurisdictional and contextual specifics. We developed an empirical approach, creating a set of prototypical scenarios that capture the diversity of current genomic data sharing practices, which allows legal and ethical analysis of key issues at a granular level. The specificity of this approach provides a strong foundation for developing useful and relevant regulatory recommendations.